2021
DOI: 10.1109/access.2021.3057586
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Cryptography With a Chaotic Map and a Multilayer Machine Learning Network for Physiological Signal Infosecurity: Case Study in Electrocardiogram

Abstract: Digital physiological signals in telecare medicine information systems have been widely applied in remote medical applications, such as telecare, tele-examination, and telediagnosis, via computer networking transmission or wireless communication. However, these medical records need to ensure authorization demands in the channel model for human body communication and remote medical servers and enhance the confidentiality, recoverability, and availability of transmission data. Hence, this study proposes a symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…To provide security to ECG signals, Lin et al [ 75 ] proposed a Multilayer Machine Learning Network (MMLN) and chaotic map that updates the network weights using back-propagation algorithm in Multilayer Perceptron Neural Network (MPNN). The authors identified that symmetric cryptographic protocols are prone to active and passive hacker attacks.…”
Section: Classification Of Secure Routing Protocols For Wbanmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide security to ECG signals, Lin et al [ 75 ] proposed a Multilayer Machine Learning Network (MMLN) and chaotic map that updates the network weights using back-propagation algorithm in Multilayer Perceptron Neural Network (MPNN). The authors identified that symmetric cryptographic protocols are prone to active and passive hacker attacks.…”
Section: Classification Of Secure Routing Protocols For Wbanmentioning
confidence: 99%
“…This framework allowed the complex and random key generations in AES without giving any consideration to the energy consumption parameter, thus ignoring one of the key constraints of WBAN. The key challenge for [ 75 ] is to secure ECG signal with the usage of GRNN and MPNN by keeping high PSNR.…”
Section: Classification Of Secure Routing Protocols For Wbanmentioning
confidence: 99%
“…For random data substitution and permutation in a 1D signal and a 2D image, we can use the chaotic map to generate a 1D bifurcation and spatiotemporal diagram, as shown in Figure 1(a), for randomly selecting chaotic sequences on the specific interval, such as sine-/ cosinepower maps, circle maps, tent maps, and logistic maps [6][7][8][9][10][11][12][13]. Its bifurcation points and chaotic trajectories can be controlled by the appropriate initial condition and control parameters.…”
Section: A Sine-power Chaotic Map (Spcm)mentioning
confidence: 99%
“…In recent years, some studies [6][7][8][9][10][11][12][13][14] have been developed for medical signal and image cryptographic applications using chaotic maps, including sine/cosine-power maps, circle maps, tent maps, and logistic maps. Chaos-based pseudorandom numbers are generated by a onedimensional (1D) chaotic map or a multi-dimensional (2D or 3D) chaotic system with the initial condition and control parameters in specific chaotic ranges, which have promising randomness properties and security levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation